Oxidation of high-temperature Cu-Al-Fe shape memory alloy - Yildiz, Koksal (Springer, 2016)
Isothermal oxidation behavior of the high-temperature Cu-13Al-5Fe (in mass, %) SMA on temperature range of 500-900 A degrees C was studied using thermo-gravimetric method. TG curve showed that the alloy has linear oxidation characteristics. From thermo-gravimetric measurements, it was determined that the alloy shows abnormal oxidation characteristics at 600 A degrees C. As K (P) values of the alloy at oxidation temperatures of 700 and 800 A degrees C were calculated as 0.00166 mg cm(-2) s(-1) and 0.0022 mg cm(-2) s(-1), respectively, K (P) value at 600 A degrees C was found as 0.0029 mg cm(-2) s(-1). DTA curve exhibited that reason of the abnormal oxidation behavior at 600 A degrees C is the endothermic reaction which causes dissolution of Fe(Al,Cu) precipitates within matrix at 568.13 A degrees C. XRD patterns of the oxidized samples were found to be compatible with the results obtained from thermo-gravimetric measurements.
Keywords: Cu-Al-Fe; Oxidation; High-temperature SMA; TG/DTA